Multi-finger localization feedback through vibrotactile sensory substitution system for prosthetic hand - Yunus, Yusof (2021)
Executing daily life activities is very challenging for those who missing their limbs due to amputation. Prosthetic technology becomes one of the alternative ways to replace the missing limb. However, recent prosthetics technology is still unable to meet the requirement of user due to less functionality especially lack of sensory feedback. This research is to develop and analyse the vibrotactile sensory substitution system for multi-finger localisation feedback. Previous study has shown the capability of vibrotactile feedback as one of the successful method. The system developed must have accessible control of many parameters such as vibratory frequency, number of active motors and sequence of stimulation. Four experiments are conducted in this research. The first experiment is to study the relationship between input duty cycle injected to the motor and the vibratory frequency produces by the actuators. Next experiment is to evaluate the finger localisation by using three parameters (vibratory frequency, vibrotactile configuration and type of actuator). The third experiment is to evaluate five different designs of vibrotactile pattern stimulation (VPS) composed of different rhythm and burst actuation time. The last experiment is to evaluate the system on slipping detection. The key outcome measures for this research are recognition rate (accuracy) and Information Transfer (IT). The results show that the higher the vibratory frequency, the better the recognition rate and IT for ERM motor with 8% difference in score. Although, there is no significant difference between LRA and ERM motor, LRA motor is chosen due to its better performance and smaller size. The best VPS in experiment three are VPS4 and VPS5 due to its high accuracy score and IT. VPS4 score is 1.79 bits and VPS5 score is 1.63 bits while the other VPS score less than 1.2 bits. The system designed is applicable for slipping detection. The findings from this research provide an enhancement for haptic feedback development in prosthetic hand.